DIGITAL IDIOMS: HOW THE INTERNET IS CREATING A NEW PHRASEOLOGY - Sharipova Madina Abduxajaxanovna,; Uktam Bakhodirovich Shukurov, (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract: The rapid expansion of internet-mediated communication has given rise to a distinct linguistic phenomenon: digital idioms. Unlike traditional idioms rooted in historical and cultural metaphors (e.g., “spill the beans”), digital idioms emerge from technological affordances, platform-specific behaviors, and meme culture. This article examines the formation mechanisms, semantic properties, and global spread of such phraseological units as “touch grass,” “gatekeep, girlboss, gaslight,” “I oop,” and “canon event.” Drawing on corpus data from Twitter (X), Reddit, and TikTok (2020–2025), we argue that digital idioms constitute a new layer of phraseology characterized by rapid obsolescence, multimodal anchoring, and cross-linguistic borrowing without translation. The findings have implications for lexicography, computational linguistics, and digital literacy education.